Grid Computing International Symposium on Grid Computing (ISGC 2007) - Lin, Simon C.; Yen, Eric.; SpringerLink (Online service) (Boston, MA : Springer US, 2009)
Grid Computing: International Symposium on Grid Computing (ISGC) 2007 is one of the most important annual events in Asia that brings together scientific contributions by world class researchers and scientists working in the Grid Computing field to exchange ideas, to present challenges, solutions and future development. The objective of this Symposium is to facilitate the information exchange as well as to explore the global collaboration and interoperation among various Grid projects. Based on the ISGC 2007, held in Taipei, Taiwan in March of 2007, this edited volume presents the latest grid solutions and research results in grid operations, grid middleware, biomedical operations, e-science applications and more. Grid Computing: International Symposium on Grid Computing (ISGC) 2007 is designed for a professional audience, composed of researchers and practitioners in academia and industry. This book is also suitable for graduate-level students in computer science. It is also one of the most important sources of Grid Computing and e-Science development in the Asia Pacific region.
Grid Activities in Asia Pacific -- Asia Federation Report International Symposium on Grid Computing 2007 -- e-Infrastructure for Taiwan and International Collaboration -- Application - High Energy Physics, Biomedicine and Life Sciences -- e-Science for High Energy Physics in Korea -- HEP Grid Computing in the UK: MOVING Towards the LHC Era -- MediGRID - Grid Computing For Medicine and Life Sciences -- Porting Biological Applications in Grid: An Experience within the EUChinaGRID Framework -- Grid Computing at Peking University in EUChinaGRID Project -- Grid Middleware & Interoperability -- ReSS: A Resource Selection Service for the Open Science Grid -- A Model for the Storage Resource Manager -- The Session Based Fault Tolerance Algorithm of Platform EGO Web Service Gateway -- Experiences with Using UNICORE in Production Grid Infrastructures DEISA and D-Grid -- Dashboard for the LHC Experiments -- Characteristics of a Novel Grid Resource Broker cum Meta-Scheduler -- Operation & Management -- Core D-Grid Infrastructure -- Monitoring the Availability of Grid Services Using SAM and Gridview -- DEISA - Cooperative Extreme Computing Across Europe -- Industry & Government -- Managing Parallel and Distributed Monte Carlo Simulations for Computational Finance in a Grid Environment.
Keywords: COMPUTER SCIENCE; COMPUTER NETWORK ARCHITECTURES; COMPUTER COMMUNICATION NETWORKS; DATA STRUCTURES (COMPUTER SCIENCE).; INFORMATION SYSTEMS; DATABASE MANAGEMENT; COMPUTER SCIENCE; COMPUTER COMMUNICATION NETWORKS; DATABASE MANAGEMENT; COMPUTER SYSTEMS ORGANIZATION AND COMMUNICATION NETWORKS; INFORMATION SYSTEMS AND COMMUNICATION SERVICE; DATA STRUCTURES; PROCESSOR ARCHITECTURES